Praktek Pendidikan Ahl Al-Shuffah pada Masa Rasulullah - Radiman, Radiman; Ainusyamsi, Fadlil Yani (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2016)
This scientific research articles have resulted in some findings. (1) The purpose of education is the ultimate goal and purpose while, students were 33 companions of Ahl al-Shuffah, educators are the Prophet Muhammad, his other self and parents, contents or educational material (human and religious, religion, beliefs, worship, morality, the Shari'ah, Qur'an, Sunnah and Ijtihad), education methods (advice, motivation, punishment, exemplary, discussion, persuasion, court, blessing, memorize, mulazamah, game), media teaching (animals, environment, body, visual, audio, column), the time and space that is anywhere and at any time of life can be implemented in education, evaluation and approval of the technical performance capabilities like Abdullah bin Mas'ud when commanded to read Al-Qur'an in front of the Prophet Muhammad. And the appointment of 'Abdullah bin Mas'ud, and Salim, the slave of Abu Hudhayfah and Ubay ibn Ka'b and Mu'adh bin Jabal as referred readings al-Qur'an, (2) the eight elements of education that is objective, learners, educators , contents, methods, teaching media, space and time, and showed a close relevance to the development of education today, education in general and education in particular with the Islamic style.